ANALISIS MELODI LAGU GASEP PADA MUSIK IRINGAN TARI BELANGKAH DI KECAMATAN NANGA MAHAP KABUPATEN SEKADAU - Rosidin, Rosidin; Djau, Nurmila Sari; Silaban, Christianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research was motivated by the importance of preserving traditional arts, especially in this study, namely Belangkah dance. The method used was a descriptive method with a form of qualitative research and using a musicology approach. Data collection technique used observation and interview techniques while the data collection tools used were interview guidelines, observational guidelines and research guidelines as well as assistive devices in the form of camcorders, mobile phones and notebooks. All data obtained in this research were analyzed using musicology review with content analysis techniques. Testing the validity of the data of this study used source triangulation techniques. The results of this study indicated that the musical scales used in the Gasep song were A minor harmonious scales on the natural basic note (A Minor), with an Adante tempo between 80-108 BPM and the bar used was 4/4 and had a three-part song form. In the melody motif there was a literal repetition, repetition at other levels (sequences up and down), magnification of the interval, decrease the interval and enlargement the value of the tone. In Gasep song there was no tone reversal (inversion). Keywords: Analysis, Gasep Song, Melody, Belangkah Dance